The use of ELISA kits for the detection of pork gelatin adulteration in food products or other: A minireview - Shausan Fairuz Jinan; Rahmi Naily Maghfiroh (Universitas Ahmad Dahlan, 2026)
Meat counterfeiting and mislabeling are important issues, especially for Muslim consumers who need halal assurance. One of the techniques used to detect pork contamination in meat products is the enzyme-linked immunosorbent test (ELISA). This method allows for the detection of specific and sensitive antigens in food samples. ELISA relies on antigen-antibody interactions to identify pork counterfeits in a variety of raw and processed meat products. Studies show that ELISA can detect pork contamination as low as 0.01-5% (w/w) in beef and poultry. The advantages of ELISA include sensitivity, specificity, quantitative, and ease of operation, making it a relevant method for the detection of pork mixing in meat products. Therefore, ELISA plays an important role as a tool for halal food surveillance and authentication of meat products in the global market. Keywords: ELISA, Halal authentication, Meat adulteration, Pork contamination.